Do IMF-Supported Programs Work? : A Survey of the Cross-Country Empirical Evidence. (IMF Working Papers; Working Paper ;, 1998)
Over the last two decades a number of cross-country empirical studies have been undertaken to assess whether IMF-supported adjustment programs have led to an improved balance of payments and current account balance, lower inflation, and higher growth. These studies use a variety of methodologies and cover different country samples and time periods. This paper critically surveys the evidence yielded by the cross-country studies, paying special attention to the pros and cons of the respective empirical methodologies employed. These studies, particularly the more recent ones, conclude that IMF-supported programs have generally been successful in stabilizing the economy.